Precision Assembly Technologies and Systems 6th IFIP WG 5.5 International Precision Assembly Seminar, IPAS 2012, Chamonix, France, February 12-15, 2012. Proceedings - Ratchev, Svetan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 6th IFIP WG 5.5 International Precision Assembly Seminar, IPAS 2012, held in Chamonix, France, in February 2012. The 15 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized into the following topical sections: micro processes and systems; handling and manipulation in assembly; tolerance management and error compensation methods; metrology and quality control; intelligent control of assembly systems; and process selection and modelling techniques.
Keywords: Computer science; Computer simulation; Computer vision; Optical pattern recognition; Engineering; Machinery; Electronics; Computer Science; Simulation and Modeling; Nanotechnology and Microengineering; Manufacturing, Machines, Tools; Electronics and Microelectronics, Instrumentation; Pattern Recognition; Image Processing and Computer Vision